Carbon‐Based Sorbents for Hydrogen Storage: Challenges and Sustainability at Operating Conditions for Renewable Energy. Issue 11 (9th May 2022) - Rimza, Tripti; Saha, Sumit; Dhand, Chetna; Dwivedi, Neeraj; Patel, Shiv Singh; Singh, Shiv; Kumar, Pradip
Abstract: It is estimated that all fossil fuels will be depleted by 2060 if we continue to use them at the present rate. Therefore, there is an unmet need for an alternative source of energy with high calorific value. In this regard, hydrogen is considered the best alternative renewable fuel that could be used in practical conditions. Accordingly, researchers are looking for an ideal hydrogen storage system under ambient conditions for feasible applications. In many respects, carbon‐based sorbents have emerged as the best possible hydrogen storage media. These carbon‐based sorbents are cost‐effective, eco‐friendly, and readily available. In this Review, the present status of carbon‐based materials in promoting solid‐state hydrogen storage technologies at the operating temperature and pressure was reported. Experimental studies have shown that some carbon‐based materials such as mesoporous graphene and doped carbon nanotubes may have hydrogen storage uptake of 3–7 wt %, while some theoretical studies have predicted up to 13.79 wt % of hydrogen uptake at ambient conditions. Also, it was found that different methods used for carbon materials synthesis played a vital role in hydrogen storage performance. Eventually, this Review will be helpful to the scientific community for finding the competent material and methodology to investigate the existing hydrogen uptake issues at operating conditions. Abstract : Hydrogen storage : The development of hydrogen storage technologies using solid materials as a storage medium is considered a promising technology as compared to compressed or liquefied hydrogen storage wherein high pressure, high‐volume containers, and low temperatures are required. This Review summarizes carbon‐based materials including carbon nanotubes, fullerene, graphene, and porous carbon for hydrogen storage at operating conditions along with various storage mechanisms.